2019
DOI: 10.1002/adma.201906626
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐ and Field‐Mediated Assembly of Magnetic Nanoparticles into High‐Aspect Ratio Crystals

Abstract: Under an applied magnetic field, superparamagnetic Fe 3 O 4 nanoparticles with complementary DNA strands assemble into crystalline, pseudo-1D elongated superlattice structures. The assembly process is driven through a combination of DNA hybridization and particle dipolar coupling, a property dependent on particle composition, size, and inter-particle distance. The DNA controls inter-particle distance and crystal symmetry, while the magnetic field leads to anisotropic crystal growth. Increasing the dipole inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Since the cubes with the 66 bp DNA design assembled with the same symmetry as spheres, we hypothesized that a similar series of morphologies would form after assembly in a field, consistent with what has been observed with spherical particles [29] . When slowed cooled as before, the morphology of the resulting crystals varied as a function of magnetic field strength from more isotropic clusters (0 G; Figure 2 c), to aligned crystals (140 G; Figure S5), and finally to defined, smooth rods (3800 G; Figure 2 e).…”
Section: Figuresupporting
confidence: 70%
See 2 more Smart Citations
“…Since the cubes with the 66 bp DNA design assembled with the same symmetry as spheres, we hypothesized that a similar series of morphologies would form after assembly in a field, consistent with what has been observed with spherical particles [29] . When slowed cooled as before, the morphology of the resulting crystals varied as a function of magnetic field strength from more isotropic clusters (0 G; Figure 2 c), to aligned crystals (140 G; Figure S5), and finally to defined, smooth rods (3800 G; Figure 2 e).…”
Section: Figuresupporting
confidence: 70%
“…A clear orientation alignment along the ⟨111⟩ SL with the field direction is observed for both samples grown inside (3800 G, Figures 4 b,d, S9) and outside a field (0 G, Figure S10 b,c). This alignment is in contrast to what is observed for spherical Fe 3 O 4 PAE crystals with bcc symmetry which have their ⟨100⟩ SL oriented along the field direction [29] . The alignment in a field also contrasts with what observed for oleate coated cubes with SC symmetry, where the ⟨100⟩ SL is oriented along the field direction and 100Fe3O4 ||⟨100⟩ SL (Figure S11, see SI for details).…”
Section: Figurementioning
confidence: 58%
See 1 more Smart Citation
“…Since the cubes with the 66 bp DNA design assembled with the same symmetry as spheres, we hypothesized that a similar series of morphologies would form after assembly in a field, consistent with what has been observed with spherical particles. [29] When slowed cooled as before, the morphology of the resulting crystals varied as a function of magnetic field strength from more isotropic clusters (0 G; Figure 2 c), to aligned crystals (140 G; Figure S5), and finally to defined, smooth rods (3800 G; Figure 2 e). The rod shape indicates that the superlattices are macroscopically aligned with respect to the applied magnetic field.…”
Section: Angewandte Chemiementioning
confidence: 89%
“…[25][26][27][28] Recent work has investigated the use of external stimuli to influence colloidal crystal growth of spherical, DNA-coated Fe 3 O 4 NPs. This work found that applying magnetic fields to the magnetic PAEs resulted in the formation of elongated nanostructures, [29] highlighting the unique ability of DNA to separate the interactions of dipoledipole coupling and DNA hybridization interactions to form high-aspect ratio structures with tailored crystal symmetry. However, the effect of nanoscale anisotropy on these interactions could not be investigated as spherical PAEs were used.…”
mentioning
confidence: 94%